Mechanical signal modulates prostate cancer immune escape by USP8-mediated ubiquitination-dependent degradation of PD-L1 and MHC-1 - Zhi-Bin Ke; Jia-Yin Chen; Yu-Ting Xue; Bin Lin; Qi Huang; Xu-Yun Huang; Dong-Ning Chen; Shao-Hao Chen; Xiao-Jian Ye; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; et al. (Cell Death and Disease)
Abstract The tumor environment of prostate cancer (PCa) tissues of high Gleason score has been proved to be more immune suppressive and has higher extracellular matrix (ECM) stiffness, but whether ECM mechanical stiffness is the cause of higher ability of invasiveness and immune escape of PCa with high Gleason score remains uncertain. In this study, we showed that higher polyacrylamide hydrogels (PAAG) stiffness resulted in the progression and immune escape of PCa via integrin β1/FAK/YAP axis. The translocation of YAP into cell nucleus to bind to TEAD2 promoted the transcriptional activation of USP8. NBR1 could be ubiquitinated, and then degraded, via interacting with P62/SQSTM1 and through autophagy-lysosome pathway. Increased expression of USP8 promoted the abundance of NBR1 via K63-linked de-ubiquitination and PD-L1 via K48-linked de-ubiquitination in response to high PAAG stiffness. NBR1-mediated selective autophagy accelerated the degradation of MHC-1 of PCa. The USP8 inhibitor presented a potential application value in sensitizing immunotherapy of PCa. Taken together, we identified a USP8-mediated de-ubiquitination mechanism that involves in the process of high PAAG stiffness-mediated high expression of PD-L1 and low expression of MHC-1 of PCa cells, which provided a rationale of immunotherapy sensitization of PCa via USP8 inhibition.